Effectiveness of anti-inflammatory agents in azoxymethane induced experimental colon cancer - Ilhan, N.; Bektas, I.; Ilhan, N.; Ozercan, I. H. (Wiley-Blackwell, 2016)
[Abstract Not Available]
41st FEBS Congress on Molecular and Systems Biology for a Better Life -- SEP 03-08, 2016 -- Kusadasi, TURKEY
Keywords: Colorectal cancer; rosmarinic acid; TAS; TOS; adiponectin